Applications of FFT for timbral characterization in woodwind instruments - Gonzalez, Yubiry; Prati, Ronaldo C. (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2021: Anais do XVIII Simpósio Brasileiro de Computação MusicalDO - 10.5753/sbcm.2021.19428, 2021)
The conceptualization of the musical timbre, which allows its quantitative evaluation in an audio record, is still an open-ended issue. This paper presents a set of dimensionless descriptors to assess the musical timbre of woodwind instruments in recordings of the fourth octave of the tempered musical scale. These descriptors are calculated from the Fast Fourier Transform (FFT) spectra using the Python Programming Language, specifically the SciPy library. The characteristic spectral signature of the clarinet, bassoon, transverse flute, and oboe are obtained in the fourth musical octave, observing the presence of degeneration for some musical sounds, that is, two given different aerophones may present the same harmonics. It is concluded that the proposed descriptors are sufficient to differentiate the aerophones studied, allowing their recognition, even in the case that there present the same set of harmonic frequencies.